Uranium (VI) Recovery from Black Shale Leaching Solutions Using Ion Exchange: Kinetics and Equilibrium Studies - Baigenzhenov, Omirserik; Khabiyev, Alibek; Mishra, Brajendra; Turan, M. Deniz; Akbarov, Merey; Chepushtanova, Tatyana (Mdpi, 2020)
This work studies the removal of uranium ions from chemically leached solutions by sorption using two weak and two strong base anionites. Batch sorption experiments were performed to evaluate the optimum conditions at pH 1.2-2.2, 1.0 g resin dose for 1-12 h contact time at room temperature. These experiments addressed sorption kinetics and sorption isotherm. The maximum sorption capacity reached 55.8 mg/g at room temperature. The kinetics data are well described by the pseudo-second-order kinetic model at initial uranium concentration of 0.62 mg.L-1. To describe sorption kinetics pseudo-first-order, pseudo-second-order and intraparticle diffusion models were proposed. Studies indicated that the sorption of uranium can be fitted by a pseudo-second-order kinetic model very well. Equilibria were described by Langmuir, Freundlich, and Dubinin-Radushkevich equations. The experimental sorption isotherm is successfully described by the Langmuir model.
Keywords: black shale ore; uranium; sorption; kinetics; equilibria